Additive for crack self-repairing of service concrete in corrosive environment and preparation method thereof

By using a combination admixture of component A and component B microspheres in concrete cracks, the synergistic effect of inorganic mineral gel and microorganisms is used to solve the problem of insufficient range of microorganism mineralization in high alkaline environments, and the self-repair and moisture blocking effect of the entire area of ​​the crack is achieved, and the service life of the concrete structure is extended.

CN119528478APending Publication Date: 2025-02-28JIANGSU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411724110.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the range of microbial mineralization activity and the self-repair effect of the full section of cracks in high alkaline environments, resulting in a shortening of the service life of concrete structures in corrosive environments.

Method used

A combination of component A microspheres and component B microspheres is used to use the admixture of component A microspheres, which include calcium sources, microorganisms and viscosity-enhancing agents, and component B microspheres include aluminum sources and viscosity-enhancing agents. Both of them are wrapped in a mixed gel layer of sulfhydryl aluminate cement-iron ore powder. Through the synergistic effect of inorganic mineral gel and microorganisms, the cracks are effectively repaired.

Benefits of technology

It significantly improves the range of microbial mineralization activities, realizes self-repair throughout the entire area of ​​the crack, improves the ability of cracks to block moisture, especially the sealing of pressure water, and extends the service life of concrete structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528478A_ABST
    Figure CN119528478A_ABST
Patent Text Reader

Abstract

The invention discloses an additive for self-repairing concrete cracks in a corrosive environment and a preparation method of the additive. The additive comprises component A microspheres and component B microspheres, the component A microspheres comprise the following substances in parts by weight: 17.74-51.9 parts of a calcium source, 8-9 parts of microorganisms and 0.5-1 part of a tackifier; the component B microsphere is prepared from the following substances in parts by weight: 28.1 to 49.51 parts of an aluminum source and 0.5 to 1 part of a tackifier; the surfaces of the component A microspheres and the component B microspheres are coated with sulphoaluminate cement-iron ore powder mixed gel layers. The microbe mineralization activity range can be remarkably widened, the distribution range of repairing products in cracks can be greatly widened through the synergistic effect of inorganic mineral gel and microorganisms, the limitation that the self-repairing depth of the microorganisms is small is broken through, self-repairing of the cracks in the whole area range is achieved, and the self-repairing effect of the whole fracture surfaces of the cracks is improved; the water blocking capability of the crack can be realized, and particularly the blocking of pressure water can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a crack admixture and a preparation method thereof, in particular to an admixture for self-repairing cracks in concrete serving in a corrosive environment and a preparation method thereof. Background Art

[0002] The treatment of concrete cracks is an important aspect of infrastructure operation and maintenance. The existence of cracks greatly reduces the service life of concrete materials. Moisture in the service environment penetrates into the cracks, providing a quick channel for the transmission of corrosive media into the interior of the concrete. The corrosive media directly reach the interior of the concrete, causing the internal hydration product phase transition and steel corrosion, which causes uneven local volume deformation of the concrete, and ultimately promotes further expansion of cracks or induces the formation of new cracks. The formation of a crack network destroys the integrity of the concrete material and greatly reduces its structural bearing capacity. Ultimately, as cracks develop, the concrete structure gradually loses its function and loses its service capacity. Therefore, timely and effective treatment of crack diseases has become the main content of concrete structure health monitoring and operation and maintenance.

[0003] In order to improve the timeliness and intelligence level of concrete crack treatment, self-healing agents with crack self-healing ability have been developed. When cracks occur in concrete, water enters the crack space to stimulate the activity of the self-healing agent, enabling it to produce a series of biological / chemical reactions and produce solid phase products to seal the crack space. The microbial self-healing method is to introduce mineralized microorganisms into the cracks and use the induced mineralization ability of the microorganisms to achieve crack sealing. However, the concrete crack solution is highly alkaline, which greatly limits the activity of microorganisms, so that the scope of microbial mineralization only exists in the surface range of the cracks. A variety of methods have been developed to improve the activity of microorganisms, such as using porous media to load microorganisms so that they exist in a relatively mild physical and chemical environment; such as using hydrogels to load microorganisms and embed them in hydrogels to avoid contact with the external highly alkaline environment; such as using domestication and strengthening methods to improve the alkali tolerance of microorganisms and improve their adaptability. In fact, the pH of the crack solution is usually as high as 13.0 or above, and it is difficult to make microorganisms adapt to such harsh conditions using domestication strategies. Although hydrogels have good water absorption capacity and rapid expansion properties, the release of water from the gel under dry conditions will cause its volume to shrink rapidly, thereby losing its crack sealing ability. The porous medium loaded with microorganisms only achieves the purpose of improving the regional environment, so that the microbial mineralization activity is confined to the interior of the porous medium.

[0004] The leakage of magnesium ions in ordinary Portland cement will produce new corrosion effects. Once the magnesium source leaks, it will react with the main hydration product CSH of the matrix to form MSH without gelling ability, and the durability of concrete will be destroyed. Therefore, it is urgent to develop effective methods to improve the physical and chemical environment of crack solutions, increase the scope of microbial mineralization activities, and enhance the self-repair effect of the entire crack section, so as to achieve the ability of cracks to block water, especially the sealing of pressurized water. Summary of the invention

[0005] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide an admixture for self-repairing cracks in concrete serving in corrosive environments with a wide range of crack self-repairing properties. Another purpose of the present invention is to provide a simple and convenient method for preparing the admixture for self-repairing cracks in concrete serving in corrosive environments.

[0006] Technical solution: The admixture for self-repair of concrete cracks in corrosive environment described in the present invention comprises microspheres of component A and microspheres of component B; the microspheres of component A comprise the following substances in parts by weight: 17.74 to 51.9 parts of calcium source, 8 to 9 parts of microorganisms, and 0.5 to 1 part of viscosity enhancer; the microspheres of component B comprise the following substances in parts by weight: 28.1 to 49.51 parts of aluminum source and 0.5 to 1 part of viscosity enhancer; the surfaces of the microspheres of component A and component B are both coated with a mixed cementitious layer of sulphoaluminate cement-iron ore powder.

[0007] Furthermore, the B component microspheres also include 4 to 5 parts of silicon source.

[0008] Furthermore, the silicon source is sodium silicate, the calcium source is calcium lactate, and the aluminum source is sodium aluminate.

[0009] Furthermore, the atomic molar ratio of calcium, aluminum and silicon in the calcium source, aluminum source and silicon source is 1:0 to 1:2.

[0010] Furthermore, the microorganisms include propionibacterium, mutualistic propionate oxidizing bacteria, and mutualistic acetate oxidizing bacteria, and the number ratio of propionibacterium, mutualistic propionate oxidizing bacteria and mutualistic acetate oxidizing bacteria is 1:1:3-4.

[0011] Furthermore, the particle size of the microspheres of component A and component B is 3.5 to 5.0 mm.

[0012] Furthermore, the thickener is any one of sodium polyacrylate, sodium alginate and polyoxyethylene.

[0013] Furthermore, the particle density of the admixture is 1900-2100 kg / m 3 .

[0014] Furthermore, the fineness of the iron ore powder is above 200 mesh.

[0015] The preparation method of an admixture for self-repairing concrete cracks in a corrosive environment according to the present invention comprises the following steps:

[0016] Step 1, preparing component A microspheres and component B microspheres with a diameter of 3.5 to 5.0 mm;

[0017] Step 2, curing the product obtained in step 1 by sprinkling water at room temperature;

[0018] Step 3, immersing the product obtained in step 2 in acrylic emulsion and drying at 40-50° C.;

[0019] Step 4: soak the product obtained in step 3 in water for 24 to 30 hours, take it out and dry it to obtain an admixture for self-repairing cracks in concrete serving in a corrosive environment.

[0020] Further,

[0021] Repair principle: First, the fracture solution environment is improved by inducing the formation of inorganic mineral gel in the fracture, creating favorable conditions for microbial activity. Secondly, the microbial mineralization activity is initiated, and by utilizing the mutual relationship between the three types of microorganisms, the substrate is metabolized in a gradient manner, and the carbon source substrate is gradually converted into calcium carbonate precipitation. Finally, the inorganic mineral gel reaction and the microbial mineralization reaction complement each other to achieve effective repair of the fracture section.

[0022] Based on the high alkalinity of the original environment of concrete cracks, calcium, aluminum and silicon sources are introduced to react with each other in the cracks to form inorganic mineral gels mainly composed of hydrated calcium aluminate and hydrated calcium aluminosilicate. The calcium aluminum mineral gel molecules usually contain a large amount of chemical water, bound water and coordinated water, and have excellent volume expansion capacity, which can effectively seal the cracks. The role of the thickener is to flocculate the generated gel particles in time to prevent them from being lost with water under flowing water conditions and increase their adhesion in the crack space. The generated hydrated calcium aluminate gel can also capture corrosive media such as free chloride ions and sulfate ions in the solution, thereby reducing their harm.

[0023] At the same time, the capture effect of the inorganic mineral gel reactor on hydroxide ions is taken into account to reduce the concentration of free hydroxide ions in the liquid phase, thereby improving the chemical environment characteristics of the fracture and providing mild conditions for the germination and growth of microorganisms. After the calcium source (calcium lactate) enters the fracture solution, the released lactate ions provide nutritional conditions for the growth of propionibacterium. Propionibacterium converts lactate ions into propionic acid and carbon dioxide. The released carbon dioxide will react to form carbonate ions in an alkaline environment, and finally combine with calcium ions to form calcium carbonate precipitation. Propionic acid will react with hydroxide ions to form propionate ions, thereby maintaining the low alkalinity conditions of the fracture. The formation of propionate ions provides favorable conditions for the growth of symbiotic propionic acid oxidizing bacteria. Propionate ions are oxidized into acetic acid molecules and carbon dioxide. Similarly, carbon dioxide will eventually be converted into calcium carbonate and deposited in the fracture space. The acetic acid molecules will continue to be used to maintain the low alkaline environmental conditions of the fracture. Acetate ions are nutrients for symbiotic acetic acid oxidizing bacteria, which will be further decomposed into carbon dioxide and eventually converted into calcium carbonate precipitation.

[0024] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0025] 1. It can significantly increase the scope of microbial mineralization activities. The synergistic effect of inorganic mineral gel and microorganisms can greatly increase the distribution range of repair products in cracks, break through the limitation of shallow depth of microbial self-repair, truly realize self-repair for the entire area of ​​cracks, improve the self-repair effect of the entire section of cracks, and realize the ability of cracks to block water, especially the blocking of pressurized water;

[0026] 2. Based on the relationship between the three types of symbiotic microorganisms, the migration and diffusion ability is good, and the gradient decomposition and utilization of the substrate lactate can be achieved, which can greatly avoid the problem of carbon dioxide gas escape caused by rapid decomposition or insufficient later repair ability;

[0027] 3. In the early stage of concrete cracking, calcium aluminate hydrate and calcium aluminosilicate hydrate gels are formed quickly, first forming a certain plugging ability inside the cracks. Aluminate and aluminosilicate gels are one of the types of concrete hydration products and have excellent compatibility. The formation of calcium aluminum mineral gels will capture and deposit a large amount of hydroxide ions, significantly reduce the pH of the crack solution, and provide suitable chemical conditions for microbial mineralization;

[0028] 4. The step-by-step decomposition of the substrate can not only maintain the low alkaline environment of the crack with the help of intermediate products, but also fully react to form calcium carbonate minerals, truly realizing the effective operation of microbial mineralization. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the component composition of the present invention;

[0030] Figure 2is a bar graph of the crack water penetration resistance repair rate of the present invention;

[0031] Figure 3 is a bar graph of the crack area repair rate of the present invention;

[0032] Figure 4 is a bar graph of the repair rate of the ultrasonic wave propagation velocity across cracks of the present invention;

[0033] Figure 5 is a bar graph of the area distribution rate of the crack surface repair product of the present invention;

[0034] Figure 6 is the XRD pattern of the repair product of the present invention;

[0035] Figure 7 It is a curve diagram of the fixing ability of the present invention for chloride ions / sulfate ions in corrosive solutions. DETAILED DESCRIPTION

[0036] Unless otherwise specified, the materials, reagents, instruments, etc. used in the following examples can be obtained from commercial sources. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0037] Sodium silicate nonahydrate, CAS: 13517-24-3, Xilong Scientific Co., Ltd. Aluminum silicate, CAS: 1302-93-8, Shanghai McLean Biochemical Technology Co., Ltd. Calcium nitrite, CAS: 13780-06-8, Shanghai Aladdin Biochemical Technology Co., Ltd. Sodium aluminate, CAS: 11138-49-1, Shanghai McLean Biochemical Technology Co., Ltd. Polyacrylamide, Henan Jiubang Water Purification Materials. Calcium lactate, CAS: 5743-47-5, Tianjin Damao Chemical Reagent Factory. Sodium alginate, CAS: 9005-38-3, Sinopharm Chemical Reagent Co., Ltd. Acrylic emulsion, Joncryl PRO 1552, BASF (China) Co., Ltd. Xylose, CAS: 58-86-6, Wuhan Xingzhongcheng Technology Co., Ltd. Polyethylene oxide, CAS: 68441-17-8, Hubei Xinghengye Technology Co., Ltd. Sodium polyacrylate, CAS: 9003-04-7, Guangdong Mingtong Biotechnology Co., Ltd. Sulphoaluminate cement, SAC 52.5, Dengdian Group Cement Co., Ltd. Portland cement, PO 52.5, Zhenjiang Beigu Conch Cement Co., Ltd.

[0038] Example 1

[0039] 100g of admixture includes 70g of inorganic mineral components (70% by mass), 1g of thickener sodium polyacrylate (1% by mass), 9g of microbial components (9% by mass), and 20g of iron ore powder (20% by mass) as a weight-bearing component.

[0040] Inorganic mineral components: 17.74g of calcium lactate powder was used as the calcium source, 4.24g of sodium silicate powder (modulus 1.4) was used as the silicon source, and 48.02g of sodium aluminate was used as the aluminum source. The molar ratio of calcium to silicon atoms was 2:1, and the molar ratio of aluminum to silicon atoms was 10:1. Microorganisms were selected from propionibacterium, mutualistic propionic acid oxidizing bacteria, and mutualistic acetic acid oxidizing bacteria, and the ratio of propionibacterium, mutualistic propionic acid oxidizing bacteria, and mutualistic acetic acid oxidizing bacteria was 1:1:3.

[0041] like Figure 1 As shown, a method for preparing an admixture for self-repairing cracks in concrete serving in a corrosive environment comprises the following steps:

[0042] Step 1: 17.74g of calcium lactate powder, 0.5g of sodium polyacrylate powder and 9.0g of microbial powder are mixed to prepare microspheres, and the outer layer is coated with a mixed cementitious material of sulphoaluminate cement and iron ore powder, and the overall particle size is not more than 4.75mm, and the obtained admixture is component A. 48.02g of sodium aluminate, 4.24g of sodium silicate and 0.5g of sodium polyacrylate powder are mixed to prepare microspheres, and the outer layer is coated with a mixed cementitious material of silicate cement and iron ore powder, and the overall particle size is not more than 5.0mm, and the obtained admixture is component B.

[0043] Step 2: Curing the product obtained in step 1 by sprinkling water at room temperature for 3 days.

[0044] Step 3: Dip the cured particles into acrylic emulsion and dry them at 50°C for 24 hours. Repeat the operation 3 times.

[0045] Step 4: After soaking the particles in water for 24 hours, taking them out and drying them, an admixture for self-repairing concrete cracks serving in a corrosive environment is obtained.

[0046] The concrete mix ratio used in the project is: cement 405kg / m 3 、Sand 756.6kg / m 3 、Stone 1080kg / m 3 , water 160kg / m 3 After testing, the volume of fine aggregate is 0.286 / m 3 , the volume of coarse aggregate is 0.386m 3 The density of fresh concrete paste is 0.966m 3 The aggregate volume is 0.672m 3 , the calculation process is as follows:

[0047] Vagg. =V f +V s =0.286+0.386=0.672m 3

[0048] The average radius of the admixture is 0.0025m and the apparent density is 2013kg / m 3 , k is 1.05. The following formula shows that the optimal dosage of admixture is 43kg / m 3 .

[0049]

[0050] According to the above calculation results, the self-repairing concrete mix ratio is comprehensively determined: cement 405kg / m 3 , admixture 43kg / m 3 、Sand 713.6kg / m 3 、Stone 1080kg / m 3 , water 160kg / m 3 Based on this, the concrete mix ratio was tested. The slump of the concrete without admixture was 185mm, and the density of the fresh slurry was 2385kg / m 3 The slump of self-repairing concrete is 180mm and the density of fresh slurry is 2380kg / m 3 The addition of admixtures has no significant effect on the conventional properties of concrete.

[0051] The prepared self-repairing concrete was cured for 28 days under standard conditions. The specimens after curing were prepared with cracks of about 1.0 mm in width according to the splitting method, and the crack width was fixed. The cracked specimens were cured under simulated tap water conditions to test the crack repair effect.

[0052] Example 2

[0053] 100g of admixture includes 80g of inorganic mineral component (80% by mass), 2g of thickener polyoxyethylene (2% by mass), 8g of microbial component (8% by mass), and 10g of iron ore powder (10% by mass) as a weight-bearing component.

[0054] Inorganic mineral components: 51.90g of calcium lactate powder is used as the calcium source, and 28.10g of sodium aluminate is used as the aluminum source. The molar ratio of calcium to aluminum is 1:1. Microorganisms are selected from propionibacterium, mutualistic propionic acid oxidizing bacteria, and mutualistic acetic acid oxidizing bacteria, and the ratio of propionibacterium, mutualistic propionic acid oxidizing bacteria, and mutualistic acetic acid oxidizing bacteria is 1:1:3.

[0055] A method for preparing an admixture for self-repairing cracks in concrete serving in a corrosive environment comprises the following steps:

[0056] Step 1: 51.90g of calcium lactate powder, 1.0g of polyoxyethylene powder and 8g of microbial powder are mixed to prepare microspheres, and the outer layer is coated with a mixed cementitious material of sulphoaluminate cement and iron ore powder, and the overall particle size is not more than 4.75mm, and the obtained admixture is component A. 28.10g of sodium aluminate and 1.0g of polyoxyethylene powder are mixed to prepare microspheres, and the outer layer is coated with a mixed cementitious material of silicate cement and iron ore powder, and the overall particle size is not more than 4.0mm, and the obtained admixture is component B.

[0057] Step 2: Curing the product obtained in step 1 by sprinkling water at room temperature for 3 days.

[0058] Step 3: Dip the cured particles into acrylic emulsion and dry them at 50°C for 24 hours. Repeat the operation 3 times.

[0059] Step 4: After soaking the particles in water for 24 hours, taking them out and drying them, an admixture for self-repairing concrete cracks serving in a corrosive environment is obtained.

[0060] The concrete mix ratio used in the project is: cement 405kg / m 3 、Sand 756.6kg / m 3 、Stone 1080kg / m 3 , water 160kg / m 3 After testing, the volume of fine aggregate is 0.286 / m 3 , the volume of coarse aggregate is 0.386m 3 The density of fresh concrete paste is 0.966m 3 The aggregate volume is 0.672m 3 , the calculation process is as follows:

[0061] V agg. =V f +V s =0.286+0.386=0.672m 3

[0062] The average radius of the admixture is 0.002m and the apparent density is 1986kg / m 3 , k is 1.06. The following formula shows that the optimal dosage of admixture is 53.6kg / m 3 For the convenience of measurement, the admixture dosage is determined to be 54kg / m 3 .

[0063]

[0064] According to the above calculation results, the self-repairing concrete mix ratio is comprehensively determined: cement 405kg / m 3 , admixture 43kg / m 3 、Sand 713.6kg / m 3、Stone 1080kg / m 3 , water 160kg / m 3 Based on this, the concrete mix ratio was tested. The slump of the concrete without admixture was 185mm, and the density of the fresh slurry was 2385kg / m 3 The slump of self-repairing concrete is 180mm and the density of fresh slurry is 2380kg / m 3 The addition of admixtures has no significant effect on the conventional properties of concrete.

[0065] The prepared self-repairing concrete was cured for 28 days under standard conditions. The specimens after curing were prepared with cracks of about 1.0 mm in width according to the splitting method, and the crack width was fixed. The cracked specimens were cured under simulated tap water conditions to test the crack repair effect.

[0066] Example 3

[0067] 100g of admixture includes 80g of inorganic mineral component (80% by mass), 2g of thickener sodium alginate (2% by mass), 8g of microbial component (8% by mass), and 10g of iron ore powder (10% by mass) as a weight-bearing component.

[0068] Inorganic mineral components: 30.49g of calcium lactate powder is used as the calcium source, and 30.49g of sodium aluminate is used as the aluminum source. The molar ratio of calcium to aluminum is 1:3. Microorganisms are selected from propionibacterium, mutualistic propionic acid oxidizing bacteria, and mutualistic acetic acid oxidizing bacteria, and the ratio of propionibacterium, mutualistic propionic acid oxidizing bacteria, and mutualistic acetic acid oxidizing bacteria is 1:1:3.

[0069] A method for preparing an admixture for self-repairing cracks in concrete serving in a corrosive environment comprises the following steps:

[0070] Step 1: 30.49g of calcium lactate powder, 1.0g of sodium alginate powder, and 8g of microbial powder are mixed to prepare microspheres, and the outer layer is coated with a mixed cementitious material of sulphoaluminate cement and iron ore powder, and the overall particle size is not more than 3.5mm, and the obtained admixture is component A. 49.51g of sodium aluminate and 1.0g of sodium alginate powder are mixed to prepare microspheres, and the outer layer is coated with a mixed cementitious material of silicate cement and iron ore powder, and the overall particle size is not more than 3.5mm, and the obtained admixture is component B.

[0071] Step 2: Curing the product obtained in step 1 by sprinkling water at room temperature for 3 days.

[0072] Step 3: Dip the cured particles into acrylic emulsion and dry them at 50°C for 24 hours. Repeat the operation 3 times.

[0073] Step 4: After soaking the particles in water for 24 hours, taking them out and drying them, an admixture for self-repairing concrete cracks serving in a corrosive environment is obtained.

[0074] The concrete mix ratio used in the project is: cement 405kg / m 3 、Sand 756.6kg / m 3 、Stone 1080kg / m 3 , water 160kg / m 3 After testing, the volume of fine aggregate is 0.286 / m 3 , the volume of coarse aggregate is 0.386m 3 The density of fresh concrete paste is 0.966m 3 The aggregate volume is 0.672m 3 , the calculation process is as follows:

[0075] V agg. =V f +V s =0.286+0.386=0.672m 3

[0076] The average radius of the admixture is 0.00175m and the apparent density is 2078kg / m 3 , k is 1.06. The optimal dosage of admixture is 56.1kg / m 3 For the convenience of measurement, the dosage of admixture is determined to be 57kg / m 3 .

[0077]

[0078] According to the above calculation results, the self-repairing concrete mix ratio is comprehensively determined: cement 405kg / m 3 、Additive 57kg / m 3 ,, sand 699.4kg / m 3 、Stone 1080kg / m 3 , water 160kg / m 3 Based on this, the concrete mix ratio was tested. The slump of the concrete without admixture was 180mm, and the density of the freshly mixed slurry was 2365kg / m 3 The slump of self-repairing concrete is 175mm and the density of fresh slurry is 2350kg / m 3 The addition of admixtures has no significant effect on the conventional properties of concrete.

[0079] The prepared self-repairing concrete was cured for 28 days under standard conditions. The specimens after curing were prepared with cracks of about 1.0 mm in width according to the splitting method, and the crack width was fixed. The cracked specimens were cured under simulated tap water conditions to test the crack repair effect.

[0080] Example 4

[0081] 100g of admixture includes 70g of inorganic mineral components (70% by mass), 1g of thickener sodium polyacrylate (1% by mass), 9g of microbial components (9% by mass), and 20g of iron ore powder (20% by mass) as a weight-bearing component.

[0082] Inorganic mineral components: 22.88g of calcium lactate powder is used as the calcium source, 27.77g of sodium aluminate is used as the aluminum source, and 22.35g of aluminum silicate is used as the silicon source. The molar ratio of calcium to silicon is 1:1, and the molar ratio of aluminum to silicon is 5:1. Microorganisms are selected from propionibacterium, mutualistic propionic acid oxidizing bacteria, and mutualistic acetic acid oxidizing bacteria, and the ratio of propionibacterium, mutualistic propionic acid oxidizing bacteria, and mutualistic acetic acid oxidizing bacteria is 1:1:3.

[0083] A method for preparing an admixture for self-repairing cracks in concrete serving in a corrosive environment comprises the following steps:

[0084] Step 1: 22.88g of calcium lactate powder, 0.5g of sodium polyacrylate powder and 9g of microbial powder are mixed to prepare microspheres, and the outer layer is coated with a mixed cementitious material of sulphoaluminate cement and iron ore powder, and the overall particle size is not more than 4.75mm, and the obtained admixture is component A. 22.35g of aluminum silicate, 27.77g of sodium metaaluminate and 0.5g of sodium polyacrylate powder are mixed to prepare microspheres, and the outer layer is coated with a mixed cementitious material of silicate cement and iron ore powder, and the overall particle size is not more than 4.75mm, and the obtained admixture is component B.

[0085] Step 2: Curing the product obtained in step 1 by sprinkling water at room temperature for 3 days.

[0086] Step 3: Dip the cured particles into acrylic emulsion and dry them at 50°C for 24 hours. Repeat the operation 3 times.

[0087] Step 4: After soaking the particles in water for 24 hours, taking them out and drying them, an admixture for self-repairing concrete cracks serving in a corrosive environment is obtained.

[0088] The concrete mix ratio used in a certain project is: cement 405kg / m 3 、Sand 756.6kg / m 3 、Stone 1080kg / m 3 , water 160kg / m 3 After testing, the volume of fine aggregate is 0.286 / m 3 , the volume of coarse aggregate is 0.386m 3 The density of fresh concrete paste is 0.966m 3 The aggregate volume is 0.672m 3 , the calculation process is as follows:

[0089] V agg. =V f +Vs =0.286+0.386=0.672m 3

[0090] The average radius of the admixture is 0.0025m and the apparent density is 2095kg / m 3 , k is 1.05. The optimal dosage of admixture is 44.8kg / m 3 For the convenience of measurement, the dosage of admixture is determined to be 45kg / m 3 .

[0091]

[0092] According to the above calculation results, the self-repairing concrete mix ratio is comprehensively determined: cement 405kg / m 3 , admixture 45kg / m 3 、Sand 711.6kg / m 3 、Stone 1080kg / m 3 , water 160kg / m 3 Based on this, the concrete mix ratio was tested. The slump of the concrete without admixture was 185mm, and the density of the fresh slurry was 2365kg / m 3 The slump of self-repairing concrete is 180mm and the density of fresh slurry is 2360kg / m 3 The addition of admixtures has no significant effect on the conventional properties of concrete.

[0093] The prepared self-repairing concrete was cured for 28 days under standard conditions. The prepared self-repairing concrete was cured for 28 days under standard conditions. The specimens after curing were prepared with cracks of about 1.0 mm in width according to the splitting method, and the crack width was fixed. The cracked specimens were cured under simulated tap water conditions to test the crack repair effect.

[0094] A simulated corrosive water environment was prepared according to the ratio of NaCl2 4.53g / L, Mg / Cl2 5.20g / L, Na2SO4 4.09g / L, CaCl2 1.16g / L, and KCl0.695g / L. Ordinary Portland cement was compounded with simulated corrosive water at a ratio of 1:10, and the supernatant was taken after standing for 24 hours to prepare a simulated solution for concrete cracks in a corrosive environment. The admixture prepared in Example 4 was ground and crushed. The admixture particle fragments were compounded with the marine concrete crack solution at a ratio of 1:5, and the concentration changes of chloride ions and sulfate ions in the crack solution were tested.

[0095] Comparative Example 1

[0096] The remaining steps of this comparative example are the same as those of Example 1, except that no aluminum source is used.

[0097] Comparative Example 2

[0098] The remaining steps of this comparative example are the same as those of Example 1, except that the mass of the microbial components is replaced by Bacillus subtilis powder.

[0099] like Figure 2 As shown, the admixtures prepared in Examples 1 to 4 have significant advantages in crack repair effect compared with Comparative Examples 1 and 2. The 28d crack water penetration repair rate prepared from the admixtures in Examples 1 to 4 all reached more than 90%, and the cracks were almost no longer leaking water. It shows that the cracks are effectively filled, the water flow channels are completely closed, and the prepared admixtures can better achieve the treatment of concrete leakage. Comparative Example 1 removes the aluminum source to avoid the formation of calcium-aluminum gel, and the repair product is not enough to fill the inside of the crack, thereby greatly reducing the repair effect. Comparative Example 2 replaces the microbial species, and relying solely on calcium-aluminum gel is not enough to produce sufficient crack repair effect. The mineralization ability of a single type of microorganism is not enough to form a good coordination effect with the inorganic gel, resulting in insufficient repair effect.

[0100] like Figure 3 As shown, the 28d crack area repair rate of the self-repairing concrete with the admixtures prepared in Examples 1 to 4 all reached more than 95%, indicating that admixtures 1-4 have good crack surface repair effects and can completely close the crack surface openings.

[0101] like Figure 4 As shown, the ultrasonic velocity recovery rate of the self-repairing concrete prepared with the admixtures prepared in Examples 1 to 4 reaches more than 70% at 28 days across the crack. The speed of ultrasonic wave propagation across the crack is related to the filling effect of the repair product inside the crack. The more the repair product inside the crack is filled, the shorter the path of ultrasonic wave propagation across the crack, and the faster the measured ultrasonic wave speed across the crack. Therefore, it can be shown that the admixture has a good effect on the internal repair of the crack.

[0102] After curing for 28 days, the concrete specimens prepared with the admixtures prepared in Examples 1 to 4 were split along the cracks to obtain crack surface images, and the ratio of the distribution area of ​​the crack surface repair product to the crack area was calculated and counted as the crack surface repair product distribution area ratio. Figure 5 As shown, the distribution area rate of self-repairing products on the crack surface of the self-repairing concrete prepared with the admixtures of Examples 1 to 4 all reached more than 75%, indicating that the admixture of the present invention has a good internal crack repair effect.

[0103] like Figure 6As shown, the repair products of the self-repairing concrete crack areas of Examples 1 to 4 were extracted for XRD testing. The results showed that there was obvious formation of calcium aluminate hydrate gel (CAH) in Examples 1 to 4, accompanied by the formation of a large amount of calcium carbonate (CaCO3). Obviously, the formation of calcium carbonate comes from the conversion of carbon dioxide produced by the metabolism of microorganisms. For Examples 1 and 4, due to the addition of silicon sources, the formation of calcium aluminosilicate hydrate gel (CASH) can also be observed. Therefore, it can be explained that the admixture played an effective role, forming a synergistic repair effect of calcium silica gel and microbial minerals.

[0104] like Figure 7 As shown, the concentration of free chloride ions and sulfate ions in the liquid phase gradually decreases, indicating that the admixture can gradually adsorb and fix chloride ions and sulfate ions that have strong corrosion ability to concrete in a simulated corrosive water environment, thereby indicating that the admixture of this embodiment can be applied to concrete structures serving in corrosive environments.

Claims

1. An admixture for self-repair of concrete cracks in corrosive environments, characterized by: The invention comprises microspheres of component A and microspheres of component B; the microspheres of component A comprise the following substances in parts by weight: 17.74 to 51.9 parts of calcium source, 8 to 9 parts of microorganisms, and 0.5 to 1 part of viscosity enhancer; the microspheres of component B comprise the following substances in parts by weight: 28.1 to 49.51 parts of aluminum source, and 0.5 to 1 part of viscosity enhancer; the surfaces of the microspheres of component A and component B are both coated with a mixed gelling layer of sulphoaluminate cement-iron ore powder.

2. The admixture for self-repairing of concrete cracks in corrosive environments according to claim 1, characterized in that: The B component microspheres also include 4 to 5 parts of silicon source.

3. The admixture for self-repairing of concrete cracks in corrosive environment according to claim 2, characterized in that: The silicon source is sodium silicate, the calcium source is calcium lactate, and the aluminum source is sodium aluminate.

4. The admixture for self-repairing of concrete cracks in corrosive environment according to claim 1, characterized in that: The atomic molar ratio of calcium, aluminum and silicon in the calcium source, aluminum source and silicon source is 1:0 to 1:

2.

5. The admixture for self-repairing of concrete cracks in corrosive environment according to claim 1, characterized in that: The microorganisms include propionibacterium, mutualistic propionate oxidizing bacteria, and mutualistic acetic acid oxidizing bacteria, and the quantity ratio of the propionibacterium, mutualistic propionate oxidizing bacteria, and mutualistic acetic acid oxidizing bacteria is 1:1:3-4.

6. The admixture for self-repairing of concrete cracks in corrosive environment according to claim 1, characterized in that: The particle size of the A component microsphere and the B component microsphere is 3.5-5.0 mm.

7. The admixture for self-repairing of concrete cracks in corrosive environments according to claim 1, characterized in that: The thickener is any one of sodium polyacrylate, sodium alginate and polyoxyethylene.

8. The admixture for self-repairing of concrete cracks in corrosive environments according to claim 1, characterized in that: The particle density of the admixture is 1900-2100 kg / m 3 .

9. The admixture for self-repairing of concrete cracks in corrosive environment according to claim 1, characterized in that: The iron ore powder has a fineness of 200 mesh or more.

10. The method for preparing an admixture for self-repairing concrete cracks in corrosive environments according to claim 1, characterized in that: The following steps are involved: Step 1, preparing component A microspheres and component B microspheres with a diameter of 3.5 to 5.0 mm; Step 2, curing the product obtained in step 1 by sprinkling water at room temperature; Step 3, immersing the product obtained in step 2 in acrylic emulsion and drying at 40-50° C.; Step 4: soak the product obtained in step 3 in water for 24 to 30 hours, take it out and dry it to obtain an admixture for self-repairing cracks in concrete serving in a corrosive environment.